An adaptive feedforward amplifier application for 5.8 GHz - (:unkn) unknown (My University, 2006)
0

In this study, a 5.8 GHz power amplifier is linearized by an adaptive feedforward technique. A DSP-based control scheme is applied to reduce the intermodulation distortion of this amplifier. A two-tone test is used to verify the design.
Keywords: Mühendislik, Elektrik ve Elektronik